Believing and Implicit Religion beyond the Churches: Religion, Superstition, Luck and Fear among 13-15 year-old Girls in Wales - Francis, Leslie J. (Implicit religion, 2006)
A sample of 1,133 year-nine and year-ten pupils (13-15 year-olds), attending six state-maintained secondary schools in South Wales, completed a survey concerned with beliefs in the afterlife, beliefs in supernatural forces, beliefs about good luck, beliefs about bad luck, beliefs about protection from harm, and fear of the supernatural. The analysis distinguishes between the belief patterns of females who belong to and attend a Christian group (the churched) and females who neither belong to nor attend any religious group (the unchurched). The data demonstrate significantly greater belief in (but no significantly greater fear of) some aspects of the supernatural among the unchurched.